The Possibility of Apologetics - Gill, J. H. (Scottish journal of theology, 1963)
Anyone who enters the batter's box of contemporary theology carrying a bat labelled ‘apologetics’ finds that he has two strikes against him before he even begins. Gone are the days when Christian apologetics held a prominent position in theological endeavour. Today such issues as the nature and situation of man, Christian ethics, the unity of the church, and the task of missions dominate the centre of the theological stage. Undoubtedly this is as it should be and it is not the purpose of this article to belittle any of these concerns. There are, however, certain observations which do bear mentioning with regard to the importance of apologetics for contemporary theology. To begin with, it should be noted that the primary purpose of all theological endeavour is to come to a better understanding of the Christian message and effectively to relate it to man and his situation. Even the above-mentioned areas of contemporary concern all have as their ultimate aim to witness to the new life in Christ. The significance of this fact is appreciated when one realises that apologetics also has this witness as its ultimate purpose. It is clear that apologetics is not unrelated to the basic theological task of this or any age.